2014
DOI: 10.1371/journal.pone.0111266
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a-3p Negatively Regulates BAFF Synthesis in Systemic Sclerosis and Rheumatoid Arthritis Fibroblasts

Abstract: We evaluated micro (mi) RNA-mediated regulation of BAFF expression in fibroblasts using two concomitant models: (i) synovial fibroblasts (FLS) isolated from healthy controls (N) or Rheumatoid Arthritis (RA) patients; (ii) human dermal fibroblasts (HDF) isolated from healthy controls (N) or Systemic Sclerosis (SSc) patients. Using RT-qPCR and ELISA, we first showed that SScHDF synthesized and released BAFF in response to Poly(I:C) or IFN-γ treatment, as previously observed in RAFLS, whereas NHDF released BAFF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 42 publications
0
41
0
Order By: Relevance
“…Instead there are 3 studies that focused on how miRNAs were involved in immune mediators’ effect on dermal fibroblasts [91, 121, 122]. Nakashima et al showed that IL-17A exert its’ anti-fibrotic effect through upregulation of miR-129-5p that downregulated COL1A1 [122].…”
Section: Epigenetic Impact In Ssc Pathogenesismentioning
confidence: 99%
“…Instead there are 3 studies that focused on how miRNAs were involved in immune mediators’ effect on dermal fibroblasts [91, 121, 122]. Nakashima et al showed that IL-17A exert its’ anti-fibrotic effect through upregulation of miR-129-5p that downregulated COL1A1 [122].…”
Section: Epigenetic Impact In Ssc Pathogenesismentioning
confidence: 99%
“…MiR-30a-3p was found to be a basic repressor of B cell-activating factor (BAFF) expression in SSc fibroblasts by Alsaleh et al; while BAFF is an important factor for B cell activation, and BAFF is overexpressed in SSc. This suggests a potential anti-fibrotic effect of miR-30a-3p (Alsaleh et al, 2014). While miR-21 was significantly upregulated in SSc fibroblasts and regulated by TGF-␤, the overexpression of miR-21 can decrease the levels of Smad7, thereby implying its therapeutic role in SSc (Zhu et al, 2013).…”
Section: Mirnas In Fibrosismentioning
confidence: 92%
“…In addition, miR-30a played a crucial role in the regulation of the autoimmune responses in rheumatoid arthritis and systemic sclerosis by blocking B cell-activating factor [50]. Moreover, miR-30a could inhibit IL-10-induced cytokine release by targeting STAT1/ MD-2(a 25kDa lipopolysaccharide-binding protein) in human monocytes [51].…”
Section: Biological Function Of Mir-30a Genementioning
confidence: 99%